2007
DOI: 10.1007/s00247-007-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of isolated right subclavian artery

Abstract: We report the MRI findings in a 3-week-old boy with D-transposition of the great arteries and an abnormal origin of the right subclavian artery from the pulmonary artery. This anomaly of the subclavian arteries is called isolation. It is infrequent in patients with a right aortic arch, but exceedingly rare in those with a left aortic arch. This is a unique report of the MRI findings in this congenital abnormality of the aortic arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The presence of an isolated right SCA arising from the pulmonary artery in association with transposition of great arteries is extremely unusual, with only a few cases reported previously. [11][12][13] The diag- SCA. To the best of our knowledge, there are 10 cases of isolated left CCA described in the literature, all having a right-sided aortic arch and aberrant left SCA.…”
Section: Association With Transposition Of Great Arteriesmentioning
confidence: 99%
“…The presence of an isolated right SCA arising from the pulmonary artery in association with transposition of great arteries is extremely unusual, with only a few cases reported previously. [11][12][13] The diag- SCA. To the best of our knowledge, there are 10 cases of isolated left CCA described in the literature, all having a right-sided aortic arch and aberrant left SCA.…”
Section: Association With Transposition Of Great Arteriesmentioning
confidence: 99%
“…As historically described, when the ductus arteriosus obliterates, the isolated SCA circulation is lost. Several cases of this phenomenon have been documented 14–18 . Additionally, Vuran et al.…”
Section: Discussionmentioning
confidence: 96%
“…Several cases of this phenomenon have been documented. [14][15][16][17][18] Additionally, Vuran et al reported a case of anomalous RSCA from the main PA in a patient with VSD and coarctation of the aorta. 19 Patients with type B IAA and severe subaortic stenosis often have anomalous origin of the RSCA from the descending aorta; 10 however, associated isolation of the RSCA in this condition is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Diagnosis is usually made using computed tomography (CT), MRI, or invasive angiography. 1,3,4,6 We report a patient with d-TGA who presents with unusual differential cyanosis, raising concerns of aortic arch anomalies, who was subsequently diagnosed with AORSA using transthoracic echocardiography (TTE). This case demonstrates the importance of considering aortic arch anomalies in d-TGA when patients do not show reverse differential cyanosis.…”
Section: Introductionmentioning
confidence: 99%